The evolution of physical performance throughout an entire season in female football players - Reyes-Laredo, F.; Pareja-Blanco, F.; López-Lluch, G.; Rodríguez-Bies, E. (Sports, 2024)
Research on the evolution of performance throughout a season in team sports is scarce and mainly focused on men`s teams. Our aim in this study was to examine the seasonal variations in relevant indices of physical performance in female football players. Twenty-seven female football players were assessed at week 2 of the season (preseason, PS), week 7 (end of preseason, EP), week 24 (half-season, HS), and week 38 (end of season, ES). Similar to the most common used conditioning tests in football, testing sessions consisted of (1) vertical countermovement jump (CMJ); (2) 20 m running sprint (T20); (3) 25 m side-step cutting maneuver test (V-CUT); and (4) progressive loading test in the full-squat exercise (V1-LOAD). Participants followed their normal football training procedure, which consisted of three weekly training sessions and an official match, without any type of intervention. No significant time effects were observed for CMJ height (p = 0.29) and T20 (p = 0.11) throughout the season. However, significant time effects were found for V-CUT (p = 0.004) and V1-LOAD (p = 0.001). V-CUT performance significantly improved from HS to ES (p = 0.001). Significant increases were observed for V1-LOAD throughout the season: PS-HS (p = 0.009); PS-ES (p < 0.001); EP-ES (p < 0.001); and HS-ES (p = 0.009). These findings suggest that, over the course of the season, female football players experience an enhancement in muscle strength and change of direction ability. However, no discernible improvements were noted in sprinting and jumping capabilities during the same period.